Ariosto Today : Contemporary Perspectives - Fedi, Roberto; Ciavolella, Massimo, 1942-; Beecher, Donald (Book collections on Project MUSE., 2003)
This collection of essays brings together twelve noted Italian and American scholars to provide a complete picture of Ariosto and all his works as an integration of tradition and invention.